AB0045 Activated rnase l as a novel disease activity biomarker in psoriatic arthritis. (12th June 2018) - Zarabi, S.K.; Hasipek, M.; Guan, Y.; Husni, E.; Ko, J.; Kontzias, A.; Jha, B.K.
Abstract : Background: Almost 60% of psoriasis (PsO) patients with psoriatic arthritis(PsA) are estimated to be untreated, undertreated or/and undiagnosed. 1 Delayed diagnosis leads to permanent joint damage causing major functional decline and diminished quality of life. However, in the absence of diagnostic biomarkers, the diagnosis of psoriatic arthritis is clinical and hence difficult to establish from non-rheumatologists. 2 Recent studies have demonstrated the upregulation of type I interferon (IFN)–inducible genes in paired peripheral blood cells (PBC) and synovial biopsies of patient with PsA. 3 Oligoadenylate synthetases (OAS) are type I IFN-stimulated family of proteins that are activators of the latent Ribonuclease L (RNase L) pathways. The OAS-RNase L system is a potent host antiviral IFN-responsive system that is completely inactive in normal conditions, but once activated mediates a broad array of pro-inflammatory cellular processes. 4 Objectives: To investigate the role of OAS–RNase L pathway in PsA; To quantify the hypothesised increased OAS–RNase L activity. Methods: To further explore the gene expression data, we developed a highly sensitive ELISA and fluorescence resonance transfer (FRET) assay to access and compare the RNase L activity in plasma and serum derived from PsA(n=10), PsO (n=10) patients or healthy control donors (n=5). Results: We found that RNase L activity was 2–3 fold higher in Pso and 3–5 fold in PsA compared to normal control (figure 1). Consistent with the gene expression analysis of upregulated type I IFN inducible genes, we also observed amplification of the downstream pro-inflammatory pathway consisting of RNase L dimer (active) and the produced cleaved RNA, which further induce IFN-B production and other inflammatory signalling. Conclusions: The proportionally increased activation of OAS/RNase L in psoriatic arthritis merits further investigation into this pathway as a potential disease activity biomarker. RNase L is an easily quantifiable enzyme that could categorise disease severity and progression in daily routine lab ordered by primary physician. The timely diagnosis is key to improved function and quality of life in PsA patients. References: [1] Lebwohl MG, et al. Patient perspectives in the management of psoriasis: results from the population-based Multinational Assessment of Psoriasis and Psoriatic Arthritis Survey. J Am Acad Dermatol2014;5:871–81.e1–30. [2] Taylor SL, et al. Rheumatologists' recommendations on what to do in the dermatology office to evaluate and manage psoriasis patients' joint symptoms. J Dermatolog Treat2009;6:350–353. [3] Dolcino M, et al. Gene Expression Profiling in Peripheral Blood Cells and Synovial Membranes of Patients with Psoriatic Arthritis. PLoS One2015;6:e0128262. [4] Chakrabarti A, et al. New insights into the role of RNase L in innate immunity. J Interferon Cytokine Res. 2011;1:49–57. Disclosure of Interest: None declared